Teacher Role as a Facilitator in Teaching Collage in ES - Marlina, Rina; Desyandri, Desyandri; Mayar, Farida (Postgraduate School, Universitas Negeri Padang, 2023)
The important teacher's role as a facilitator in teaching college in elementary schools is to facilitate the development of students' creativity and understanding. The purpose of this article is to investigate the teacher's role as a facilitator in teaching college in elementary schools and identify approaches, strategies, and best practices in facilitating effective college learning. The research method used in this study was interviews with five teachers and an analysis of the relevant literature. The results of the study show that the facilitator's approach is very important in directing students in the creative process and exploring collage techniques. Effective strategies and practices include providing concrete examples, using step-by-step guides, and engaging students in reflection and discussion regarding their collage work. This study also revealed that teaching collage can improve students' understanding and skills in the art of collage and has a positive impact on students' self-confidence. This article provides practical guidance for teachers in teaching college in elementary schools, encourages the development of student's artistic potential, and establishes the teacher's role as an effective facilitator.